Low-intensity pulsed ultrasound stimulation facilitates in vitro osteogenic differentiation of human adipose-derived stem cells via up-regulation of heat shock protein (HSP)70, HSP90, and bone morphogenetic protein (BMP) signaling pathway. Issue 3 (22nd May 2018) - Zhang, Zhonglei; Ma, Yalin; Guo, Shaowen; He, Yi; Bai, Gang; Zhang, Wenjun
Abstract : Low-intensity pulsed ultrasound (LIPUS) has positive effects on osteogenic differentiation. However, the effect of LIPUS on osteogenic differentiation of human adipose-derived stem cells (hASCs) is unclear. In the present study, we investigated whether LIPUS could promote the proliferation and osteogenic differentiation of hASCs. hASCs were isolated and osteogenically induced with LIPUS stimulation at 20 and 30 mW cm −2 for 30 min day −1 . Cell proliferation and osteogenic differentiation potential of hASCs were respectively analyzed by cell counting kit-8 assay, Alizarin Red S staining, real-time polymerase chain reaction, and Western blotting. The results indicated that LIPUS stimulation did not significantly affect the proliferation of hASCs, but significantly increased their alkaline phosphatase activity on day 6 of culture and markedly promoted the formation of mineralized nodules on day 21 of culture. The mRNA expression levels of runt-related transcription factor, osteopontin, and osteocalcin were significantly up-regulated by LIPUS stimulation. LIPUS stimulation did not affect the expression of heat shock protein (HSP) 27, HSP40, bone morphogenetic protein (BMP)-6 and BMP-9, but significantly up-regulated the protein levels of HSP70, HSP90, BMP-2, and BMP-7 in the hASCs. Further studies found that LIPUS increased the mRNA levels of Smad 1 and Smad 5, elevated the phosphorylation of Smad 1/5, and suppressed the expression of BMP antagonist Noggin. These findings indicated that LIPUS stimulation enhanced osteogenic differentiation of hASCs possibly through the up-regulation of HSP70 and HSP90 expression and activation of BMP signaling pathway. Therefore, LIPUS might have the potential to promote the repair of bone defect.